COMPULSIVE BUYING AND ELDERLY MEN: DEPRESSION, COPING STRATEGIES AND SOCIAL SUPPORT - Varveri, Loredana; Novara, Cinzia; Petralia, Valentina; Romano, Floriana; Lavanco, Gioacchino (European Scientific Journal, ESJ, 2014)
Old age is characterized by great changes that become real challenges that the person must overcome in order to effectively end his evolutionary process. Particulary, the most stressful events for the elderly are the social economic decline, the deterioration of health and the loss of loved ones. It is therefore important to consider the strategies chosen by the elderly person to cope with such tasks; these strategies, if not effective, result in a developmental failure. The objective of this research was to analyze the relantionship among geriatric depression, coping strategies and levels of problematic shopping in elderly male subjects. The research involved 120 men over 60’. The choice of only elderly men is related to the idea that compulsive buying – which is usually associated with young people and females – is rarely examined in men because we generally think that they can cope better with critical events that women, using manly coping strategies (such as sport, gambling etc.). The shopping in its problematic form, affects 29% of involved subjects and becomes the means used to avoid coping with feelings and dealing with problems directly. The research finds a significant correlation between problematic shopping and depression, prooving in this way the existence of a link between how the person truly feels about his life and the use he does in relation with that of the shopping it self.